Bankintermediation bei der Kreditvergabe an junge oder kleine Unternehmen - Susanne Prantl; Matthias Almus; Jürgen Egeln; Dirk Engel (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2006)
Loan financing, especially long term bank loan financing, is important for young or small firms in Germany. A large share of all small business lending in Germany originates in public financing programs and cooperative banks, (non-cooperative) private sector credit banks as well as savings banks mediate in the assignment of loans from these programs. Our empirical analyses of this loan type provide insights into the small business loan assignment behavior of the three different bank groups in general. Using various econometric techniques, observation periods and data sources - including detailed data on 6.880 firms - we find three robust, originate results: Not only recently, but already at the beginning of the 1990s credit banks played no substantial, statistically significant role in small business lending. Cooperative and savings banks have, in contrast, a strong, significant positive influence on young, small firms' loan access. In addition, the loan assignment behavior of the two latter groups is found to be very similar. This is an important result given the ongoing controversial discussion on reforming the German savings bank sector.
urn:nbn:de:bvb:19-epub-13373-1
Keywords: 330; Kreditvergabeverhalten von Genossenschaftsbanken; Kreditbanken und Sparkassen; Finanzierung junger; kleiner Unternehmen; langfristige Kredite und öffentliche Förderprogramme; Reformierung des deutschen Sparkassensektors